Latino Caregiver Experiences With Asthma Health Communication. (January 2015) - Riera, Antonio; Ocasio, Agueda; Tiyyagura, Gunjan; Krumeich, Lauren; Ragins, Kyle; Thomas, Anita; Trevino, Sandra; Vaca, Federico E.
In this article, we analyze qualitative data from a purposeful sample of limited English proficiency (LEP) asthma health caregivers. We used ethnically concordant, semistructured, in-depth Spanish-language interviews and a follow-up focus group to explore issues related to communication during pediatric asthma encounters in medical settings. Inductive coding of Spanish transcripts by a bilingual research team was performed until thematic saturation was reached. Several key findings emerged. LEP caregivers encountered significant asthma burdens related to emotional stress, observed physical changes, and communication barriers. Language-discordant communication and the use of ad hoc interpreters were common. This finding is complex, and was influenced by perceptions of interpreter availability, delays in care, feelings of mistrust toward others, and individual emotional responses. Language-concordant education and suitable action plans were valued and desired. We discuss a revealing depiction of the LEP caregiver experience with asthma health communication and recommend areas for further inquiry.